Symphalangism, short stature, skeletal anomalies, and accessory testis: a new malformation syndrome. - Theodor, R (1979)
A 17-year-old Jewish Sephardi male is described with symphalangism, short stature, multiple skeletal anomalies, and an accessory testis, which appears to be a new malformation syndrome of possible genetic aetiology.